The Hermeneutics of the Socinian Atheology of the Polish Brethren. Introduction of a Democratic Political Philosophy - Paradowski, Ryszard; Paradowska, Wiera (Hybris, 2023)
The paper discusses the arguments in favor of the proposition that an atheistic concept is not just one where “God does not exist” (in a sense bequeathed on it by theologies) but also one where, despite a declarative belief in the idea of God understood in religious terms, it formulates its creed in a socio-cultural and axiological order in ways that diametrically contradict a view of God seen as the supreme level of an absolute hierarchy, embodiment of an absolute power and an exclusive competence to defining good and evil. In this understanding, atheism is an outlook, holding that the world is built non-hierarchically and there is no one absolute authority. Thus seen, the ideology of the Polish Brethren is atheistic (despite a theistic declaration).